Peningkatan Literasi dan Pemahaman Tentang Wakaf Uang bagi Para Dosen dan Tenaga Kependidikan di Lingkungan Sekolah Tinggi Islam: Increasing Literacy and Understanding of Cash Waqf for Lecturers and Educational Personnel in the Islamic College Environment - Hendra Wijaya; Azwar, Azwar (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2024)
Cash waqf has become a financial instrument that has great potential for advancing community welfare and strengthening the foundations of various development programs aimed at improving the quality of life in the community, including educational development. In this context, active participation from all levels of society, including educators or teaching staff, for example lecturers and education staff, is crucial in ensuring the success of cash waqf programs. This community service activity aims to increase literacy and understanding regarding cash waqf among lecturers and education staff through a Webinar on the Socialization of the Cash Waqf Movement for Lecturers and Education Staff in Islamic Colleges, taking place at the College of Islamic Sciences and Languages Arabic (STIBA) Makassar. The method used in carrying out community service activities is face-to-face lectures (socialization) through stages or activity flows, namely: observation, preparation, implementation, and evaluation. The results of this community service activity show that the participants looked enthusiastic and showed high interest in contributing to the cash waqf movement through KAWAN WAHDAH. Based on the evaluation results, it appears that this socialization can increase understanding and literacy regarding cash waqf, especially among the academic community in the STIBA Makassar environment. After this activity, the participants are expected to be able to actively contribute to becoming cash waqf through KAWAN WAHDAH or other programs. Keywords: cash waqf, lecturer, Kawan Wahdah, STIBA Makassar